2016
DOI: 10.1155/2016/8675836
|View full text |Cite
|
Sign up to set email alerts
|

Intake, Nutrient Apparent Digestibility, and Ruminal Constituents of Crossbred Dorper × Santa Inês Sheep Fed Diets with Babassu Mesocarp Flour

Abstract: The aim of this study was to evaluate the effect on intake, apparent digestibility, and ruminal constituents of sheep in response to the addition of increasing levels of babassu mesocarp flour (BMF) to the diet. Twenty crossbred sheep (29.17 ± 2.23 kg) were used in a randomized complete block design. Lambs were confined for 21 days, with 16 days for diet adaptation and 5 days for data collection, in which they were fed an isonitrogenous diet (16.5 ± 0.2 CP, DM basis) containing 70% of concentrate and 30% (DM b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Although changes in kinetics of fermentation have been reported to result in a decrease of ruminal fermentation [4,24] and NDF digestibility [3] with BMF addition, because of the higher acid detergent fiber (ADF) content [25] in BMF, in this study, the NDF digestibility increased linearly.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Although changes in kinetics of fermentation have been reported to result in a decrease of ruminal fermentation [4,24] and NDF digestibility [3] with BMF addition, because of the higher acid detergent fiber (ADF) content [25] in BMF, in this study, the NDF digestibility increased linearly.…”
Section: Discussionmentioning
confidence: 66%
“…It has been suggested that goats have a higher number of cellulolytic bacteria [8] and microbial protein production [26]. These factors could contribute to the results that differed from results reported with lambs [3]. However, the rate of digestion was related more to the diet than to the animal species consuming the diet [27].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations